Teacher Physical Self-Concept Implementation Training at SDN Pejuang V Bekasi City - Halim, Abdul; Manurung, Alberth Supriyanto (Abdimas Indonesian Journal, 2024)
The objective of this study is to examine the potential benefits of incorporating physical self-concept training into the professional development of educators at SDN Pejuang V in Bekasi City. The physical self-concept is a significant element of teacher personality development, capable of influencing not only teaching performance but also interactions with students. To investigate this, qualitative research methods were employed, with data collected through in-depth interviews, observation, and document analysis. The findings indicated that the training had a beneficial effect on teachers' comprehension of the physical self-concept and its practical application in daily activities. Consequently, it is recommended that similar training be implemented in other schools to enhance teachers' professionalism.